Police Authority and the Role of Traffic Infrastructure in Law Enforcement Against Traffic Violations in Badung District - Putra, Made Andrey Dwipayana; Sihotang, Erikson; Subawa, Mulyawan (West Science Law and Human Rights, 2025)
Police authority and the role of traffic infrastructure are very important in law enforcement against traffic violations in Badung Regency. The police act as law enforcers in charge of regulating, guarding, escorting, and patrolling traffic. Traffic infrastructure, such as signs, road markings, and traffic lights, support the police in regulating and controlling traffic flow. Obstacles to Law Enforcement Against Traffic Violations in the Badung Resort Police, including: a. lack of cars available to conduct traffic patrols. b. lack of traffic police personnel. c. lack of traffic patrol hours. d. lack of cooperation from the community to realize the condition of the traffic. lack of cooperation from the community to realize orderly, safe and smooth traffic conditions, including: a) Riders who run away at high speed during traffic operations b) Riders never feel deterrent even though they have repeatedly committed traffic violations c) The number of people who inform information about traffic operations to other motorists so that other motorists are reluctant to pass through roads that are being held traffic operations. d) Always abuse the position of parents, family and relatives when conducting traffic operations.